FAKTOR-FAKTOR PENYEBAB DOSEN TIDAK BERMINAT MELAKUKAN PENELITIAN - Nina Pratiwi, Athur; Chasanatum, Fida; Wahyudi Utomo, Supri (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2013)
Orientation: Basic research is one of the types of research programs established by the Higher Education and LPPM DP2M PGRI Madiun Teachers Training College that aims to provide as Tri Darma university for lecturers.Research Purpose: The objectives of this research were to establish studentsâ abillity in reading several theories from international journal articles and writingÂ  an analyzing composition for their academic eading and writing skills.Motivation for the study: The research provides some factors comes from outside and inside the lecturers that make them have no motivation to do a research.Reasearch design, Approach, and Method: This study begins with the creation of a questionnaire instrument for lecturers randomly selected study program of 13 study programs available. The instrument is made in a set of questions that consists of three categories of questions. The first category is a question of personal condition lecturer, then questions relating to external encouragement, and the last category was largely on the encouragement. Of the 75 questionnaires were distributed a number of 68 respondents of the questionnaire returns. Descriptive analysis and comparison of literature review (review journal) done to sharpen the reasoning of the data collected.Main Findings: The main results of this research culminated with some opinions that can be used for further study: first, most of the lecturers are high productivity physical condition with age range between 24 to 39 years old, have little income less than or equal to 2 million dollars per month, and have experience of working on campus is more than two years. Second, extrinsic motivation among lecturers include: Research is the number of credit obligations to academic rank; Studies program, faculty, and the environment in which it provided the impetus for research performance is quite good, but has not been matched with a senior pioneering in the neighborhood; and financial satisfaction from the new research is felt by a few lecturers. Third, intrinsic motivation is as follows: Most of the lecturers do not yet have the expertise groove (Road Map) research, yet have a match between the courses of teaching with research materials, as well as supporting research have not felt for lectures his subject; The notion that research is an additional burden in addition to the burden of the family, teaching, and administrative opinion is not held by the lecturers; Ability to organize and plan the faculty research time has not been good; The willingness of faculty to engage students and concern for the environment scholarly ability Prodi is still not enough; In quantitative research methods, some professors feel no difficulty in analyzing the data. In fact, 10 of them felt good to have the ability to do so; Qualitative research skills mastered by the majority of the faculty; There is no clarity in the mastery of the ability to conduct research faculty mixture; Most of the lecturers feel difficulty in international publication owned research results, and is a barrier to separate the circles.Contribution/Value-add: In this study, the results of the study could give an idea of motivation among faculty researching interest in Madiun PGRI Teacher Training Institute, which in the future could be a reference for research programs and other programs.